1988
DOI: 10.1200/jco.1988.6.8.1254
|View full text |Cite
|
Sign up to set email alerts
|

Early stage ovarian cancer: a randomized clinical trial comparing whole abdominal radiotherapy, melphalan, and intraperitoneal chromic phosphate: a National Cancer Institute of Canada Clinical Trials Group report.

Abstract: Two hundred fifty-seven eligible patients with stage I, IIA "high risk" ovarian carcinoma and IIB, IIIO (disease confined to pelvis), were randomized to either total abdominal radiotherapy (arm A) 2,250 rad in 20 fractions (107 patients), melphalan (arm B) 8 mg/m2/d X 4 every 4 weeks X 18 courses (106 patients), or intraperitoneal chromic phosphate (arm C) 10 to 20 mCi (44 patients). All patients were initially treated with pelvic radiotherapy; arm A, 2,250 rad in ten fractions; and arms B and C, 4,500 rad in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

1991
1991
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(23 citation statements)
references
References 20 publications
0
20
0
3
Order By: Relevance
“…Chlorambucil and Ara-C are part of an effective regimen for the treatment of low-grade non-Hodgkin's lymphomas; 34 high-dose melphalan and high-dose Ara-C are both active in advanced non-Hodgkin's lymphomas; 35,36 and finally, melphalan and gemcitabine are active against ovarian and breast cancers. [37][38][39][40] In addition, Ara-C, a drug that inhibits DNA repair, has been reported to enhance the cytotoxic activity of melpha-lan. 41 Hence, conferring chemoprotection against the hematotoxicity produced by nitrogen mustards and cytosine nucleoside analogs could potentially allow the safe use of desirable drug combinations that might otherwise cause unacceptable hematopoietic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorambucil and Ara-C are part of an effective regimen for the treatment of low-grade non-Hodgkin's lymphomas; 34 high-dose melphalan and high-dose Ara-C are both active in advanced non-Hodgkin's lymphomas; 35,36 and finally, melphalan and gemcitabine are active against ovarian and breast cancers. [37][38][39][40] In addition, Ara-C, a drug that inhibits DNA repair, has been reported to enhance the cytotoxic activity of melpha-lan. 41 Hence, conferring chemoprotection against the hematotoxicity produced by nitrogen mustards and cytosine nucleoside analogs could potentially allow the safe use of desirable drug combinations that might otherwise cause unacceptable hematopoietic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…A surgical staging procedure was not described in the protocol of five trials and these studies have been excluded from the meta-analysis (15)(16)(17)(18)(19) (Table 2).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Those who had extensive adhesions at surgery were treated with whole abdominopelvic RT rather than 32 P. The overall incidence of bowel obstruction requiring surgery was 5%. The National Cancer Institute (NCI) Canada study [18] demonstrated significant bowel toxicity in patients who were treated with pelvic RT and 32 P; 9% of patients experienced small bowel obstruction, resulting in early closure of the treatment arm.…”
Section: Chemotherapy Vs 32 Pmentioning
confidence: 99%